Upaya Peningkatan Pengetahuan Masyarakat terhadap Covid-19 Menggunakan Media Poster - Masruroh; Kiki Septaria; Elva Hidayatul Haque (TAAWUN, 2022)
The ongoing Covid-19 pandemic has caused various efforts to prevent this Covid-19 such as public education, which is still necessary to be carried out. The purpose of this service activity is to provide information to the public about Covid-19 as well as to increase public knowledge about Covid-19. The method used in this activity is giving education to the public about Covid-19 using posters and distributing questionnaires to get the data of public knowledge regarding Covid-19 such as its symptoms, spread, prevention, and treatment. These posters and questionnaires were distributed to 3 target villages in Lamongan with 30 residents as respondents. Evaluation of this activity is carried out by considering the result of public knowledge after distributing posters. The result of the implementation of this activity showed that the average public knowledge about Covid-19 has increased by 29%. Thus, it can be said that this activity was successfully conducted and can help the public to get information about Covid-19 as an effort to prevent Covid-19.